Hooliganism as a problem of public order in the Ukrainian SSR in the early 1950s (Law and Safety, 2023)
The article examines the topical and insufficiently studied in historical and legal science issue of the factors that caused hooliganism in the early 1950s, the level of this type of crime in the main regions of Ukraine at that time and some steps taken by the Ministry of Internal Affairs of the Ukrainian SSR to reduce hooliganism. Hooliganism occupied one of the main positions in the list of offences committed by young people. The factors of hooliganism had their roots in the years of war and post-war devastation, which were the childhood and adolescence of the majority of those who committed crimes under the relevant article “Hooliganism” of the Criminal Code of the Ukrainian SSR.The complex events of this time certainly affected the psyche and psychology of these people: they saw violence in all its forms, often being brought up in the absence of their father, who was at the front. The famine of 1946–1947, malnutrition during the war, lack of proper living conditions, and often housing, also affected their psyche. Their educational and cultural levels were also insufficient. The age of these hooliganism perpetrators was 18-25 years old, which also influenced their behaviour and actions. The incompletely formed character and marginality inherent in young people generally played a negative role in their development as positive individuals. Homelessness and neglect of children and adolescents played a detrimental role in the escalation of hooliganism in the 1950s. The war and post-war devastation deformed the normal process of initial socialisation of children and adolescents, which had a detrimental effect on the set of social roles and cultural norms they learned and served as one of the reasons for the rise in hooliganism in peacetime. The amnesty of March 1953 did not improve the political situation in the country and only worsened the crime situation. Hooliganism became widespread among urban working-class youth, especially among the social group that lived in dormitories and worked on construction sites of industrial enterprises, i.e., was mostly unskilled labour.The memorandum by the Minister of Internal Affairs of the Ukrainian SSR T. Strokach to the first secretary of the CPSU Central Committee O. Kyrychenko dated 30 September 1953 contains numerous facts of hooliganism in Donetsk, Kharkiv, Kryvyi Rih, Dniprodzerzhynsk, Sievierodonetsk and other cities of the republic. These facts show that hooliganism was often senseless and cruel, led to more serious crimes (murder, rape), and was usually committed while under the influence of alcohol. According to the criminal law doctrine of that time, it was believed that there were no socio-economic reasons for hooliganism, and that its manifestations arose as a result of shortcomings in law enforcement and youth education. But this was an erroneous point of view, an attempt to hide from the real problems.
Keywords: Ukraine; 1950s; Ministry of Internal Affairs; police; hooliganism.